Creation of voice database, acoustic analysis and standardisation of normal indian voices - LATHADEVI H T; MALIPATIL SR; S P GUGGARIGOUDAR (International Journal of Pharma and Bio Sciences, 2017)
Acoustic analysis is used to assist differential diagnosis, documentation and evaluation of treatment for voice disorders. Clinical data have shown that jitter and simmer are indices of voice pathology or perceptual hoarseness but are more commonly used as an outcome measure.A voice with some periodicity can now be analyzed with a computerized acoustic analyzer, a relatively newer technique that can be widely used in the clinical practice.The purpose of the study was to create a normative Indian voice database and propose a standardization for normal acoustic parameters for Indian voices. 1000 Normal voice samples were collected from college students (male and female) aged 18-28 yrs. A sustained vowel /a/ was recorded and analyzed for parameters like Jitter, Shimmer, Harmonic noise ratio and Fundamental frequency (Fo) using a software. The Mean, SD, range of the voice parameters were calculated from the sample voices. The value of ranges of mean Jitter was 0.00 to 0.03635, mean Shimmerwas 0.06 to 0.2506 and Harmonic Noise Ratio was 8.31 to 30.73db.